Analysis of Midwife Service Accessibility at Health Centers in East Pontianak District through Spatial GIS Modeling - Pratiwi, Dian Ayu; Ulfah, Maria; Harjanti, Diah Trismi (GEOREFERENCE, 2024)
Technology innovation has become the key to providing and disseminating information in the current era of globalization. One such innovation is Geographic Information Systems (GIS), which enables the development, storage, management, and visualization of geographic location-related information. In the context of basic healthcare services, GIS is utilized to map the availability of midwifery services in community health centers (Puskesmas), focusing on East Pontianak District. This research employs geospatial analysis methods, utilizing statistical data and GIS techniques. The analysis reveals disparities in the distribution of midwifery services in East Pontianak District. Although some community health centers have nearly met service standards, there are still areas that require special attention in fulfilling midwifery services. The midwifery service accessibility map provides a clear visual representation of the distribution and availability of midwifery services in the area. Color-coding on the map indicates the level of service availability, with areas in light pink nearing the standard, dark red requiring special attention, and yellow zones indicating unmet needs. Recommendations to enhance midwifery workforce needs evaluation by considering workload and population ratios are expected to aid in crafting more precise and effective healthcare policies to ensure optimal healthcare delivery for the community.